Faktor yang Berhubungan dengan LOS Pasien Bedah Orthopedi - Rahman, Abdul; Ibrahim, Kusman; Rahayu, Urip (Journal of Telenursing (JOTING), 2023)
This literature review aims to analyze what factors are associated with LOS in orthopedic surgery patients. This literature review was carried out using PRISMA guidelines, the electronic databases used were ScienceDirect, CINAHL and Pubmed with the keywords "Length of Stay' OR 'Hospital Discharge' OR 'Hospital Stay' AND 'Orthopaedic Surgery". The results obtained were 10 full text articles, using English, and published in the period 2013-2023. Based on the articles, five groups of factors were found, namely: respondent characteristics (gender and age), comorbidities, surgical time, social support, and attendance at preoperative education classes. Conclusion, Predicting LOS in surgery is an important factor because it helps hospitals provide quality surgical services, ensure patient safety, and plan optimal resources for patients. Further research is still needed to identify factors that influence the LOS of orthopedic surgery patients, especially in Indonesia. So we can find the right solution to reduce the LOS of orthopedic surgery patients. Keywords: Orthopedic Surgery, Length of Stay, Length of Stay